Risk of cancer in patients with fecal incontinence - Adelborg, Kasper (Cancer Med, 2019)
BACKGROUND: Fecal incontinence may be an early symptom of cancer, but its association with cancer remains unclear. We examined the risk of selected cancers, including colorectal cancer, other gastrointestinal cancers, hormone‐related cancers, and lymphoma, in patients with fecal incontinence. METHODS: Using Danish population‐based registries, all patients with hospital‐based diagnoses of fecal incontinence during 1995‐2013 were identified. We calculated cumulative incidences of cancers. As a measure of relative risks, we computed standardized incidence ratios (SIRs), that is, the observed number of cancers relative to the expected number based on national incidence rates by sex, age, and calendar year. RESULTS: Among 16 556 patients with fecal incontinence, the cumulative incidence of colorectal cancers, other gastrointestinal cancers, hormone‐related cancers, and lymphoma each was less than 0.4% after 1 year. It increased to under 3% after 10 years. The SIR for any cancer during 19 years of follow‐up was 1.12 [95% confidence interval (CI), 1.06‐1.19]. The SIRs during the first year were 2.31 (95% CI, 1.65‐3.13) for colorectal cancer, 1.56 (95% CI, 0.89‐2.54) for other gastrointestinal cancers, 1.00 (95% CI, 0.72‐1.35) for hormone‐related cancers, and 2.02 (95% CI, 1.01‐3.61) for lymphoma. Beyond 1 year, the SIR reached unity for other gastrointestinal cancers, hormone‐related cancers, and lymphoma, while a reduced risk was observed for colorectal cancer (SIR = 0.77, 95% CI, 0.59‐0.98). CONCLUSIONS: Fecal incontinence was a marker of cancer, especially gastrointestinal cancers and lymphoma within 1 year, which presumably is driven partly by reverse causation. However, the absolute risks were low. Heightened diagnostic efforts may explain in part the increased short‐term risk of colorectal cancers.